Overview of Organic Amendments for Management of Plant-Parasitic Nematodes, with Case Studies from Florida - McSorley, Robert (The Society of Nematologists, 2011)
Organic amendments have been widely used for management of plant-parasitic nematodes. Relatively rapid declines in nematode population levels may occur when decomposing materials release toxic compounds, while longer-term effects might include increases in nematode antagonists. Improved crop nutrition and plant growth following amendment use may lead to tolerance of plant-parasitic nematodes. Results depend on a great variety of factors such as material used, processing/composting of material, application rate, test arena, crop rotation and agronomic practices, soil type, climate, and other environmental factors. Reasons for variable performance and interpretation of results from amendment studies are discussed. Case studies of amendments for nematode management are reviewed from Florida, where composts and crop residues are the most frequently used amendments. Plant growth was often improved by amendment application, free-living nematodes (especially bacterivores) were often stimulated, but suppression of plant-parasitic nematodes was inconsistent. Amendments were generally not as effective as soil fumigation with methyl bromide for managing root-knot nematodes (Meloidogyne spp.), and often population levels or galling of root-knot nematodes in amended plots did not differ from those in non-amended control plots. While amendments may improve plant growth and stimulate soil food webs, additional study and testing are needed before they could be used reliably for management of plant-parasitic nematodes under Florida conditions.